2016
DOI: 10.3389/fphys.2016.00356
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate and Respiratory Rate Influence on Heart Rate Variability Repeatability: Effects of the Correction for the Prevailing Heart Rate

Abstract: Background: Since heart rate variability (HRV) is associated with average heart rate (HR) and respiratory rate (RespRate), alterations in these parameters may impose changes in HRV. Hence the repeatability of HRV measurements may be affected by differences in HR and RespRate. The study aimed to evaluate HRV repeatability and its association with changes in HR and RespRate.Methods: Forty healthy volunteers underwent two ECG examinations 7 days apart. Standard HRV indices were calculated from 5-min ECG recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 50 publications
(124 reference statements)
4
58
0
3
Order By: Relevance
“…This non-invasive method is widely used in clinical and experimental researches (Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology, 1996; Lombardi and Stein, 2011), and normalized HRV parameters (HF%, LH%, LH/HF) were effective to evaluate muscle sympathetic nervous activity (Pagani et al, 1997). However, recent reviews argue that meaning of these HRV indices is more complex in that both LF and HF components may be modulated not only by sympathetic and parasympathetic neural activity but also by other non-autonomic nervous factors (Lombardi and Stein, 2011; Billman, 2013; Heathers, 2014; Gasior et al, 2016), which should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…This non-invasive method is widely used in clinical and experimental researches (Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology, 1996; Lombardi and Stein, 2011), and normalized HRV parameters (HF%, LH%, LH/HF) were effective to evaluate muscle sympathetic nervous activity (Pagani et al, 1997). However, recent reviews argue that meaning of these HRV indices is more complex in that both LF and HF components may be modulated not only by sympathetic and parasympathetic neural activity but also by other non-autonomic nervous factors (Lombardi and Stein, 2011; Billman, 2013; Heathers, 2014; Gasior et al, 2016), which should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to calculation of the spectral HRV parameters, the Kubios default smoothness priors detrending was employed (Lambda, λ value = 500) as previously described (Tarvainen et al, 2014; Gąsior et al, 2016). The IBIs were transformed to evenly sampled time series with 4-Hz interpolation resampling rate.…”
Section: Methodsmentioning
confidence: 99%
“…The detrended and interpolated IBIs were used for the frequency-domain HRV analysis. HRV spectra were calculated by using the fast Fourier transform (FFT) with Welch’s periodogram method (50% overlap window and 300 s window width) as previously described (Gąsior et al, 2016). We reported the low-frequency (LF) (0.04–0.15 Hz) and HF (high-frequency) power (0.15–0.40 Hz) and the LF/HF ratio as previously described (Task Force of the European Society of Cardiology and the North American Society of Pacing Electrophysiology, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it was asserted that HRV parameters increase fundamentally with decreasing HRs and increasing IBIs due to mathematical and physiological reasons (M. Boyett et al, 2019;M. R. Boyett, 2017;Gąsior, Sacha, Jeleń, Zieliński, & Przybylski, 2016;Monfredi et al, 2014;Sacha, 2013). Boyett et al concluded that high HR levels with steep pacemaker potentials produce relatively (little variability between successive heart beats) small changes in the IBI, whereas low HR levels with flat pacemaker potentials produce relatively large changes in the IBI (M. Boyett et al, 2019).…”
Section: Relationship Between Ibi and Hrvmentioning
confidence: 99%